ANTI-LIPASE AND MCF-7 BREAST CANCER CELL PROLIFERATION INHIBITION IN VITRO OF THE EXTRACT-ENRICHED POLYPHENOLS AND SAPONINS FROM Musa balbisiana FRUIT - Huyen, Nguyen Thi Thu; Dieu, Dinh Khanh; Tram, Nguyen Huynh; Nhon, Hoang Thi Ngoc (HUIT Journal of Science, 2024)
Musa balbisiana is one of the most widely used bananas, and its parts have been used in medicine worldwide. This study aimed to determine the anti-lipase and the inhibition of MCF-7 breast cancer cells proliferation of the polyphenol and saponin-enriched extract from M. balbisiana fruit. The potent anti-lipase activity of the extract was observed via an assay for pancreatic lipase, and the anticancer activity of the extract was assessed through its anti-proliferative ability on MCF-7 breast cancer cells by sulforhodamine B assay. This study concluded that the extract had high lipase and MCF-7 cell inhibition with IC50 values of 48.82 ± 1.21 μg/mL and 289.5 ± 8.7 μg/mL, respectively. These results suggest that the obtained extract from M. balbisiana fruit might have the potential to be used as an agent to support obesity reduction and inhibit breast cancer cell proliferation.